Application of silver nanoparticles in the modification of polymers - Wenda, M.; Jeziórska, R.; Zielecka, M.; Panasiuk, M. (Polimery, 2021)
This paper is a review of the literature related to the preparation methods for silver nanoparticles and effects of the synthetic conditions on the properties of nanosilver. Particular attention is paid on the antibacterial properties of silver nanoparticles and their possible use in polymer composites. Such materials can be applied in the production of medical and household articles as well as in the building sector. Also, the biocidal properties of colloidal silver solutions, methods for controlling the stability of colloidal silver particles and limitations of using these materials are described.